Posttraumatic Stress Disorder and Depressive Symptoms: It’s Prevalence and the Role of Stigma as a Mediating Factor in Help-Seeking Behaviours among University Students in Sarawak - Faizul, Adenan (Universiti Malaysia Sarawak (UNIMAS), 2020)
The present study investigated Posttraumatic Stress Disorder (PTSD), depressive symptoms and its relationship with stigma and help seeking behavior among university students in Sarawak. The high prevalence of mental disorders among university students has been investigated in Malaysia but the study on PTSD is almost none. Meanwhile, an attempt was made to improve the study of depressive symptom in this study. Stigma towards mental disorders sufferers are still strong in this country including among our university students. Strong stigma may lead to unwillingness in help seeking behavior. A cross-sectional research design was conducted; a non-probability sampling was used with a total number of 624 students from 3 different higher institutions in Sarawak participated in this study. A pilot study was conducted prior to the actual study. All participants were briefed with issues of confidentiality and their rights. The Research and Ethics Committee, Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak approved this study. Results showed that at least 88% of the participant reported of having at least one direct or indirect trauma experience. The five most prevalent trauma exposure overalls (direct and indirect) were road accident (67.4%), loss of a family member (by death) 62.6%, serious illness (32.7%), almost drowning (29.9%) and divorce (28.6%). There was significantly more male than female in experiencing certain types of trauma. Results showed that 17.9% students reported exhibiting PTSD symptoms and 20% students reported having depressive symptoms. Both male and female students exhibited equal score of PTSD and depressive symptoms. Those who have PTSD tend to report significant depressive symptoms as well. Results also showed that 51.9% have high stigma. Both genders have the same score of stigma regardless of their mental health status. Of 624 participants, only 41.9% reported that they would likely to seek help when they have personal problem. Female (75.1%) were more likely to seek help as compared to male (24.9%). The three main help sources for those who have personal and emotional problem were parent, intimate partner, and mental health professional. Those with PTSD tend to report higher score for help seeking behavior. However, students who have depressive and without depressive symptoms equally have similar score in help seeking behavior. Multiple regression analyses also show that stigma does not play a mediator role for PTSD or depressive students in help-seeking behaviors. Some implications of this research finding were discussed in relation to clinical practices and research. Several suggestions and recommendations were also presented in order to improve future research.